Diversity of gall-inducing insect associated with a superhost plant species: Plant architecture, resource availability and interspecific interactions - Marcilio Fagundes; ÉLLEN MARIANE SANTOS Santos; Karen Duarte; Larisa Santos; Jaqueline Vieira; Cirilo Oliveira; Priscila Souza Silva (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fagundes M, Santos EML, Duarte KLR, Santos LM, Vieira JS, Oliveira CHD, Silva PS. 2020. Diversity of gall-inducing insect associated with a superhost plant species: Plant architecture, resource availability and interspecific interactions. Biodiversitas 21: 1182-1189. The role of interspecific competition in the organization of herbivorous insect communities may vary depending on resource availability. Trees are structurally more complex and have greater resource availability for herbivorous insects than shrubs. In this study, we evaluated the roles of plant architecture and interspecific interactions on community organization of the gall-inducing insect associated with trees (adult plants) and shrubs (young plants) of Copaifera langsdorffii. Our results showed that the species composition of gall-inducing insect communities associated with C. langsdorffii differed statistically between trees and shrubs. In addition, the trees presented greater diversity of gall-inducing insects than the shrubs, corroborating the hypothesis of plant architecture. The results of the analysis of null models showed that the co-occurrence of gall-inducing insect species associated with trees not differ from the co-occurrence predicted by chance. Thus, interspecific interactions cannot be used to explain the community organization of the gall-inducing insects on C. langsdorffii trees. On the other hand, the co-occurrence of gall-inducing insect species differed from the co-occurrence predicted by chance when shrubs plants were analyzed, indicating that biotic interactions can shape the structure of the gall-inducing insect community on shrubs. The lower availability of oviposition sites probably generates a dispute for these resources among females of different species of gall-inducing insects only in the shrubs. Therefore, the role of competition in the organization of herbivore insect communities on their host plant may vary depending on the ontogenetic stage of the host plant.